The future is faster than you think : how converging technologies are transforming business, industries, and our lives - Diamandis, Peter H; Kotler, Steven, 1967- (Simon & Schuster, 2020)
"From the New York Times bestselling authors of Abundance and Bold comes a practical playbook for technological convergence in our modern era"--